2020
DOI: 10.1016/j.colegn.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Fostering graduate nurse practice readiness in context

Abstract: Background: The healthcare environment is highly pressured, dynamic and demanding of staff. Existing research indicates that when graduate nurses begin work, they are not practice ready and struggle to adapt and manage their responsibilities as registered nurses. Aim: As part of a larger study, this paper examines the impact of the healthcare environment on graduate nurses' practice readiness and the factors that assist them to become practice ready. Method: Multiple case study design with 67 participants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…These discoveries were then seen as confirmation that RallytheWorld satisfied the uniqueness criteria in order to be considered as an instrumental case warranting further investigation (Harrison, Birks, Franklin, & Mills, 2017).…”
Section: Case Selectionmentioning
confidence: 85%
“…These discoveries were then seen as confirmation that RallytheWorld satisfied the uniqueness criteria in order to be considered as an instrumental case warranting further investigation (Harrison, Birks, Franklin, & Mills, 2017).…”
Section: Case Selectionmentioning
confidence: 85%
“…The idea of being ready to practice is based on a multidimensional concept that includes personal, professional, clinical, and industrial factors ( Harrison et al, 2020a ) and continues to develop after graduation as a nurse. Factors that can influence the student being ready to practice include the effectiveness of academic clinical experiences and paid healthcare positions while in school ( Harrison et al, 2020b ). The quality of the educational experience (didactic, clinical, and simulation) is not completely understood, and it has been identified that there is a need for more robust research for how to prepare the next generation of nurses for the clinical setting ( Currie et al, 2022 ; Ironside et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the program was developed, the CNI competencies were streamlined to meet the GN role scope criteria. This subgroup was particularly mindful of the transition process and the factors that influence and enhance the traditional newly licensed nurse's transition into practice 2 . Under normal circumstances, new nurses experience stress when transitioning to the role of professional nurse, but it was recognized that the pandemic added new challenges.…”
Section: Introductionmentioning
confidence: 99%
“…This subgroup was particularly mindful of the transition process and the factors that influence and enhance the traditional newly licensed nurse's transition into practice. 2 Under normal circumstances, new nurses experience stress when transitioning to the role of professional nurse, but it was recognized that the pandemic added new challenges. The transition to practice for newly licensed RNs has been well-studied, but there is no existing literature on utilizing a new-graduate unlicensed nurse in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%